CORRELATION BETWEEN PROLONGED INTERNET USAGE AND ACHIEVEMENT MOTIVATION AMONG UNDERGRADUATES IN ENUGU STATE, NIGERIA - Onwa, Ignatius I. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2022)
Motivation is an essential component of the educational ecosystem that has received much research attention. Achievement motivation is an aspect of the motivational concept that is widely correlated with academic achievement. However, there are intimations that the increase in internet technologies exerts pressure on individuals and might potentiate the variation in achievement motivation. The present study examined prolonged internet usage as a correlate of achievement motivation among undergraduates. A convenient sample of two hundred and sixty-seven students pooled from public tertiary institutions in Enugu State, Nigeria, participated in the study. The respondents completed a self-report measure of the achievement motivation and Chen's internet addiction scale. was a statistically significant, moderate positive correlation between prolonged internet usage and achievement motivation, r (265) = .42, p < .001. Most importantly, observation of the R2 revealed that prolonged internet usage explained about 21% of the variation in achievement motivation. The result and recommendations are discussed.